Satisfaction level of students in the design and Implementation of a virtual simulation laboratory in the Department of Pharmacology, Faculty of Medicine at UNMSM - Placencia Medina, Maritza Dorila (2015)
Objective: Todesign and build an educational model using a Virtual Simulation Laboratory Section of Pharmacology and to know the level of student satisfaction. Material and Methods: Descriptive, qualitative study of research-action type. The design and implementation of a virtual simulation laboratory, the intervention of improvement and perfection of teaching materials for the development of thepractical section of Pharmacology, Faculty of Medicine at San Marcos was planned, using the software Microlab® and CV Rat. A survey of user satisfactionin virtual laboratory technique was conducted, using the interview as aninstrument, and a Likert scale of minimum satisfaction starting in 1 to maximum of 10. Sample size of 26 students. Results: A new process of Experimental Pharmacology Laboratory teaching - learning was implemented, using virtual simulation. Most students in the virtual class room lab have a satisfaction level 9-10 / 10 on the Likert scale. Conclusion: The implemented virtual simulation laboratory in the Section of Pharmacology, efficiently stimulates the learning of the actors of this process, with a good level of student satisfaction.